Breast fibromatosis: Making the case for primary vs secondary subtypes. Issue 4 (20th August 2019) - Ghanta, Swapna; Allen, Ahkeel; Vinyard, Alicia Huff; Berger, Rachel; Aoun, Jessica; Rosenkrantz Spoont, Jamie; Avisar, Eli
Abstract: Fibromatosis of the breast is a rare condition that can be locally aggressive. The mainstay of treatment remains wide local excision, with varied adjuvant therapy as needed. The authors describe their experience in the treatment of a series of patients and propose the classification of primary and secondary breast fibromatosis. A single‐institution retrospective analysis of patients treated for breast fibromatosis from 2003 to 2017 was completed. Demographic data, pertinent past medical history, and treatment modalities were reviewed. Primary breast fibromatosis was defined as arising in the absence of previous surgery or radiation therapy to the ipsilateral breast. Secondary breast fibromatosis was defined as arising in the setting of previous surgery or radiation therapy to the ipsilateral breast. A total of 16 patients were included with the median age 40 (28‐64) years. The average size of the lesion was 6.37 cm (range of 1.5‐15 cm). Mean follow‐up time was 65 months. Surgical excision was completed in 14 patients, with two recurrences. There were no recurrences in patients with surgical margins >1 cm. Two patients were treated nonsurgically. There were seven patients with primary fibromatosis of the breast and nine patients with secondary fibromatosis of the breast. Fibromatosis of the breast is difficult to diagnose prior to surgical excision. We advocate for the multi‐disciplinary treatment of this disease process with an aggressive surgical approach to achieve margins >1 cm.